2020
DOI: 10.1002/jhbp.841
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of superb microvascular imaging of ultrasound for diagnosis of gallbladder lesion

Abstract: Gallbladder (GB) cancer (GBC) is a malignancy with a poor prognosis. The 5-year survival rate of unresected GBC is approximately 0%, and the 3-year survival rate of advanced GBC remains at <20% even after curative resection. 1,2 To improve the prognosis of GBC, proper diagnosis with imaging study is essential. Gallbladder cancer usually presents as a protruded lesion or wall thickening. However, some GB lesions, such as in the case of cholecystitis or adenomyomatosis, also present as a protrusion or wall thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…There is only one report on the utility of SMI as a microvascular imaging technique for gallbladder lesions. In this study, which Kin et al reported that a change in the caliber of vessels significantly predicted malignant gallbladder lesions [ 30 ]. This result is consistent with that of this study.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one report on the utility of SMI as a microvascular imaging technique for gallbladder lesions. In this study, which Kin et al reported that a change in the caliber of vessels significantly predicted malignant gallbladder lesions [ 30 ]. This result is consistent with that of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Superb microvascular imaging with US using perfluorobutane showed irregularly branched microvessels (Video S2). 2 Bile cytological examination after endoscopic transpapillary gallbladder drainage showed no atypical cells. Though the polyps were suspected to be benign, laparoscopic cholecystectomy was performed according to the patient’s preference.…”
Section: Figurementioning
confidence: 97%
“…An initial study including 20 patients also evaluated the feasibility of contrast-enhanced superb microvascular imaging for the vascular evaluation of gallbladder lesions (Fig. 3 ) demonstrating a significantly higher frequency of tortuous microvessels and abrupt caliber change in malignancies comparted to benign gallbladder lesions [ 37 ].
Fig.
…”
Section: Gallbladder Pancreatic and Splenic Applicationsmentioning
confidence: 99%
“…FNH: spoke-wheel pattern (41–67%). HCC: non-specific or irregular pattern (48–93%) Assessment of treatment response [ 18 ] Detection of residual intratumoral flow after transarterial chemoembolization Fibrosis staging [ 25 28 ] Vascular changes can predict the severity of fibrosis Diagnosis of steatosis [ 29 ] Vascular index inversely correlated with hepatic steatosis Assessment of liver transplant recipients [ 30 33 ] Improved visibility of the hepatic artery and diagnosis of hepatic artery thrombosis Gallbladder Diagnosis of acute cholecystitis [ 34 ] Superb microvascular imaging value predicted acute cholecystitis Diagnosis of gallbladder lesions [ 37 ] Superb microvascular imaging may help in the differential diagnosis Kidney Differential diagnosis between renal lesions [ 41 45 ] Improved detection of intratumoral vascularization. Malignant tumors: annular or ring-like flow pattern (65–67%) Diagnosis of acute pyelonephritis [ 46 ] Improved detection and diagnosis Evaluation of renal function [ 47 , 48 ] Cortical flow and vascular index correlated with the severity of chronic kidney disease Bladder Acute cystitis [ 50 ] Higher vascular index was associated with acute cystitis Vesicoureteral reflux [ 51 ] Demonstrated reversed ureteral jet and/or renal pelvic swirl sign Prostate Diagnosis of prostate cancer [ 52 , 53 ] Higher vascularity in malignant lesions and lesions with...…”
Section: Introductionmentioning
confidence: 99%